2009
DOI: 10.1007/s12272-009-1415-7
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol inhibits Porphyromonas gingivalis lipopolysaccharide-induced endothelial adhesion molecule expression by suppressing NF-κB activation

Abstract: P. gingivalis is a major pathogen that is involved in the onset and progression of periodontal disease. This study investigated the effect of resveratrol, a naturally occurring polyphenol, on P. gingivalis LPS-accelerated vascular inflammation, a key step in the progression of periodontitis. Resveratrol significantly inhibited the P. gingivalis LPS-induced adhesion of leukocytes to endothelial cells and to the aortic endothelium by down-regulating the cell adhesion molecules, ICAM-1 and VCAM-1. Moreover, the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
52
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 31 publications
3
52
0
1
Order By: Relevance
“…There are several pioneering reports on RSV, including studies on the inhibition of the arachidonate metabolism via interactions with the 5-lipoxygenase and cyclooxygenase pathways in leukocytes [6][7][8][9][10][11][12] . However, RSV attracted little interest until 1979, when the "French Paradox" 13 reported the positive benefit of an RSV-containing diet, in particular the moderate consumption of red wine, for coronary heart disease.…”
Section: Introductionmentioning
confidence: 99%
“…There are several pioneering reports on RSV, including studies on the inhibition of the arachidonate metabolism via interactions with the 5-lipoxygenase and cyclooxygenase pathways in leukocytes [6][7][8][9][10][11][12] . However, RSV attracted little interest until 1979, when the "French Paradox" 13 reported the positive benefit of an RSV-containing diet, in particular the moderate consumption of red wine, for coronary heart disease.…”
Section: Introductionmentioning
confidence: 99%
“…The main mechanism suggested for inhibition of LPS by resveratrol is non-activation of the nuclear factor of KB (NF/KB) (26). Sirtuin proteins (SIRT) are thought to improve mitochondrial function and energy limiting, there is a direct relationship between SIRT and the beneficial role of resveratrol including the improvement of glucose metabolism and insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…In one study carried out by Nafumi et al, the effects of resveratrol were investigated on Wistar male rats with periodontal disease, and it was shown that resveratrol reduced periodontitis and bone loss, increased antioxidant defense, and improved inflammatory factors; therefore, resveratrol supplementation was recommended for improving periodontal status (47). In a laboratory study in Korea, Joo Park et al (2009) investigated the effect of resveratrol on lipopolysaccharide P. gingivalis, and suggested that resveratrol supplementation may help to remove periodontal pathogens (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Park H.J. и соавторы устано-вили, что экспрессия молекул адгезии ICAM-1 и VCAM-1 на эндотелиоцитах микрососудов чело-века блокируется ресвератролом путем ингибиро-вания активации NF-kB [18].…”
unclassified